Intrapersonal Conflict of the Main Character “Draupadi” in Yaagyasenee - K.C., Usha (Journal of Janta Multiple Campus, 2024)
The focus of this research is in the area of intrapersonal conflict faced by the main character in Pratibha Ray's Yaagyasenee. It has presented how Draupadi, the most misunderstood character of epic Mahabharat suffers from intrapersonal conflict due to various reasons in the novel. This study is important in order to discover how an individual fall in the trap of intrapersonal conflict in a normal life, when own goals, values or roles diverge with others. The research approach adopted in this research article includes qualitative method. It links literature to the society and the context. The article concentrates on intrapersonal conflict in Draupadi which has been studied using different patterns of conflict identified by Kurt Lewin. This research article explains that while fulfilling their responsibilities or utilizing their rights, people have to continuously pass through intrapersonal conflict which makes different impacts in their lives. It is useful for the researchers who want to study any art from intrapersonal perspectives.